The Great Powers and Global Struggle, 1490-1990 - Rasler, Karen A., 1952- (Book collections on Project MUSE., 2009)
In The Great Powers and Global Struggle, Karen A. Rasler and William R. Thompson focus on two themes: the rise and fall as well as the relative decline of major world powers over the past five hundred years, and the way in which these processes have set the stage for the outbreak of global war. Their interdisciplinary approach encompasses political science, economics, sociology, geography, and history. The most significant wars occur when regional leaders -- historically in Western Europe -- challenge global leaders. By studying the wars of Napoleon, Louis XIV, Phillip II and the Italian/Indi.